A rare case of gestational thyrotoxicosis as a cause of acute myocardial infarction. (16th November 2016) - Nannaka, Varalaxmi Bhavani; Lvovsky, Dmitry
Summary: Angina pectoris in pregnancy is unusual and Prinzmetal's angina is much rarer. It accounts for 2% of all cases of angina. It is caused by vasospasm, but the mechanism of spasm is unknown but has been linked with hyperthyroidism in some studies. Patients with thyrotoxicosis-induced acute myocardial infarction are unusual and almost all reported cases have been associated with Graves' disease. Human chorionic gonadotropin hormone-induced hyperthyroidism occurs in about 1.4% of pregnant women, mostly when hCG levels are above 70–80 000 IU/L. Gestational transient thyrotoxicosis is transient and generally resolves spontaneously in the latter half of pregnancy, and specific antithyroid treatment is not required. Treatment with calcium channel blockers or nitrates reduces spasm in most of these patients. Overall, the prognosis for hyperthyroidism-associated coronary vasospasm is good. We describe a very rare case of an acute myocardial infarction in a 27-year-old female, at 9 weeks of gestation due to right coronary artery spasm secondary to gestational hyperthyroidism with free thyroxine of 7.7 ng/dL and TSH <0.07 IU/L. Learning points: AMI and cardiac arrest due to GTT despite optimal medical therapy is extremely rare. Gestational hyperthyroidism should be considered in pregnant patients presenting with ACS-like symptoms especially in the setting of hyperemesis gravidarum. Our case highlights the need for increased awareness of general medical community that GTT can lead to significant cardiac events. Novel methods of controlling GTT as well as medical interventions like ICD need further study.